Developmental assays using invasive cane toads, Rhinella marina, reveal safety concerns of a common formulation of the rice herbicide, butachlor. (1st March 2021) - Shuman-Goodier, Molly E.; Singleton, Grant R.; Forsman, Anna M.; Hines, Shyann; Christodoulides, Nicholas; Daniels, Kevin D.; Propper, Catherine R.
Abstract: Identifying the adverse impacts of pesticide exposure is essential to guide regulations that are protective of wildlife and human health. Within rice ecosystems, amphibians are valuable indicators because pesticide applications coincide with sensitive reproductive and developmental life stages. We conducted two experiments using wild cane toads ( Rhinella marina ) to test 1) whether environmentally relevant exposure to a commercial formulation of butachlor, an acetanilide herbicide used extensively in rice, affects amphibian development and 2) whether cane toad tadpoles are capable of acclimatizing to sub-lethal exposure. First, we exposed wild cane toads to 0.002, 0.02, or 0.2 mg/L of butachlor (Machete EC), during distinct development stages (as eggs and hatchlings, as tadpoles, or continuously) for 12 days. Next, we exposed a subset of animals from the first experiment to a second, lethal concentration and examined survivorship. We found that cane toads exposed to butachlor developed slower and weighed less than controls, and that development of the thyroid gland was affected: exposed individuals had smaller thyroid glands and thyrocyte cells, and more individual follicles. Analyses of the transcriptome revealed that butachlor exposure resulted in downregulation of transcripts related to metabolic processes, anatomic structure development, immune system function, and response to stress. Last, we observed evidence of acclimatization, where animals exposed to butachlor early in life performed better than naïve animals during a second exposure. Our findings indicate that the commercial formulation of butachlor, Machete EC, causes thyroid endocrine disruption in vertebrates, and suggest that exposure in lowland irrigated rice fields presents a concern for wildlife and human health. Furthermore, we establish that developmental assays with cane toads can be used to screen for adverse effects of pesticides in rice fields. Graphical abstract: Image 1 Highlights: Realistic exposure to butachlor affected development of cane toad tadpoles. Animals developed slower, weighed less, and the thyroid gland was affected. Non-monotonic response; low concentration, 0.002 mg/L, produced the largest effects. Exposure caused extensive downregulation of transcripts. Cane toad tadpoles can acclimatize to some herbicide exposures. Abstract : Environmentally relevant exposures to a commercial formulation of butachlor, an herbicide used extensively in rice, affect development, morphology, and gene expression of cane toad tadpoles. Developmental assays with cane toad tadpoles can be used to screen for adverse effects of pesticides in rice fields.